2019
DOI: 10.1021/acs.molpharmaceut.9b00337
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Transdermal Delivery of Buprenorphine Hydrochloride and Naltrexone Hydrochloride by Iontophoresis

Abstract: The opioids buprenorphine hydrochloride (BUP) and naltrexone hydrochloride (NTX) show promise as a combination treatment for addiction, but no means of delivering the two compounds in one medicine currently exist. In this paper, we report sufficient input rates of both these drugs from one iontophoretic transdermal drug delivery system. Experiments were performed using dermatomed pig skin mounted in glass side-bi-side cells. BUP and NTX were iontophoretically delivered together from the anode using direct cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The skin permeation rate was measured using a horizontal diffusion cell (PermeGear). 21 , 22 All test compounds were dissolved in 3.84 mM isopropyl myristate. We used the β2 adrenergic receptor agonist tulobuterol as a percutaneous positive control.…”
Section: Methodsmentioning
confidence: 99%
“…The skin permeation rate was measured using a horizontal diffusion cell (PermeGear). 21 , 22 All test compounds were dissolved in 3.84 mM isopropyl myristate. We used the β2 adrenergic receptor agonist tulobuterol as a percutaneous positive control.…”
Section: Methodsmentioning
confidence: 99%
“…By passing an electrical current through the skin, this technique serves to enhance skin permeability, as well as allow positively charged compounds to be transported into the skin by the resulting electric field. Though various groups are developing iontophoresis-based transdermal delivery methods for both small molecule- and peptide-based drugs [100,101], the topic is seemingly not undergoing active research within Canada.…”
Section: Discussionmentioning
confidence: 99%
“…An electric current (typically <0.5 mA/cm 2 ) is applied on the skin to drive the charged molecule by the electrophoresis force, along with the resulting electroosmotic flow from ions in the solvent 3 . Recent study on the iontophoresis drug delivery have clearly demonstrated the effectiveness and the advantages of this technique 4‐12 …”
Section: Introductionmentioning
confidence: 99%